Implementasi Pembelajaran Anak Slow Learner Pada Masa Pandemi di Sekolah Amanah Bunda Tangerang Selatan - Lisyafaati Hij Nabila.P; Nur Dian Andini; Rizkya Kamelida Fitriani (Fakultas Tarbiyah IIQ Jakarta, 2022)
Education is one of the most important program that made by government. The government said the necessary things to put every child at school for at least 9 years. This rule includes normal and special needs kids. For the special needs child, the government provides a special system for the education called inclusive education. There are several kids categorized as a special needs child one of them is a slow learner. This slow learner child experiences obstacles or delays in thinking in several ways, responding to stimuli and adapting, but is better than mentally retarded, slower than normal. Slow learners in the classroom need longer study time than their peers. .the purpose of this study was to determine the teacher's efforts in guiding slow learner children. This research method uses qualitative methods by using a qualitative field approach and library research.